Pengaruh Jarak terhadap Efektivitas Komunikasi Antarpribadi (Studi Pada Mahasiswa Komunikasi Penyiaran Islam FDIK UIN IB - Riza Nurfitri; Neni Efrita; Lidya Arman; Prima Kurinati Hamzah (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Relationships between children and parents are so familiar or often communicate face to face because they live in one house. When far away the closeness of parents and children is still maintained as if they lived in one house or not. Basically, parents and children must want to communicate even if they are just asking to let go of homesickness. The purpose of this study is to find out and explain the effect of openness on long distance relationships, to determine the effect of empathy for long distance relationships, and to determine the effect of support for long distance relationships. This study uses quantitative research methods. Data collection techniques used were questionnaires. The questionnaire used has passed the validity test. Questionnaires were distributed to 42 respondents selected from 168 populations using random sampling techniques. The data obtained is processed using the SPSS data processing program. The results obtained were analyzed using descriptive analysis techniques. The results that can be taken from this study are: (1) aspects of self-openness to long distance relationships are normal that self-disclosure does not have a significant relationship to long-distance relationships. (2) the aspect of empathy for long distance relationships is normal but the results of empathy are not related to long distance relationships. (3) aspects of support for long distance relationships are normal and support does not affect long distance relationships.